2016
DOI: 10.1111/glob.12141
|View full text |Cite
|
Sign up to set email alerts
|

The boundaries of transnationalism: the case of assisted voluntary return migrants

Abstract: Few studies on transnationalism have focused on migrants who return to their country of origin with insufficient resources and limited mobility. This study sheds light on the transnational connections of those who went back to Georgia and Armenia from Belgium on a voluntary assisted return and reintegration programme. Using Boccagni’s (2012) analytical framework, we reveal the returnees’ interpersonal, institutional and symbolic transnational ties. Although these ties were often limited and had little effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
0
14
0
2
Order By: Relevance
“…Supporting social and personal connections, making investments in the infrastructure of the former home location, or sending remittances home gives returnees visibility back in the former home country and among related communities, creates high social status, and assists in future reintegration. Lietaert et al (2017) specified that remittances may act as a strategic investment, aimed at improving living conditions in a place where a migrant plans to settle in the future. It is common for migrants who aspire to return to use remittances to build a house or purchase another property in their former country of origin; for instance, in Dakar, Senegal, 'the majority of building projects are initiated and sustained by transnational migrants who send money to families, business partners, and contractors in the city' (Melly 2010: 39).…”
Section: Return Migrationmentioning
confidence: 99%
“…Supporting social and personal connections, making investments in the infrastructure of the former home location, or sending remittances home gives returnees visibility back in the former home country and among related communities, creates high social status, and assists in future reintegration. Lietaert et al (2017) specified that remittances may act as a strategic investment, aimed at improving living conditions in a place where a migrant plans to settle in the future. It is common for migrants who aspire to return to use remittances to build a house or purchase another property in their former country of origin; for instance, in Dakar, Senegal, 'the majority of building projects are initiated and sustained by transnational migrants who send money to families, business partners, and contractors in the city' (Melly 2010: 39).…”
Section: Return Migrationmentioning
confidence: 99%
“…Remittances, visits home, transnational political and cultural activities, as well as everyday communication between distant family members are all highly stratified because they depend on the availability of ICT infrastructures and resources and on the class, gender and legal status of the migrants in question (Boccagni 2012;Carling et al 2012;Lietaert et al 2017;Wilding 2006). Parreñas (2005), for example, showed that the capacities of middle-class Filipinas and those employed in domestic service to keep in touch with their loved ones differ.…”
Section: Revisiting the Literature On Transnational Families And Expementioning
confidence: 99%
“…Adjustment is linked to several outcomes that are of relevance for organizations, while it is also valued on its own. In addition, repatriates' self-concept or more specifically their cultural or international identity and sense of belonging is increasingly recognized as being an important factor associated with their adjustment (Lietaert, 2017;Chiang et al, 2018) Accordingly, literature on repatriates takes into account that international mobility can result in profound personal transformations, which might consequently influence psychological comfort on re-entry.…”
Section: Psychological Comfort: Psychological and Temporal Understandmentioning
confidence: 99%
“…Lastly, some authors have also pointed out that people's wish or desire to re‐migrate, which in relation to the narrow conceptualization of sustainable return is often used as an indicator of unsuccessful re‐entry has a weak correlation to actual remigration (Koser and Kuschminder, ). Furthermore, the idea of returning to the former host country can merely illustrate a longing to stay connected to this country rather than a wish to return and resettle there (Lietaert et al., ).…”
Section: The “Succesful” Re‐entry Of Refugees and Asylum Seekersmentioning
confidence: 99%